The EIB Climate Survey 2019-2020 - European Investment Bank (European Investment Bank, 2020)
The European Investment Bank has launched a large scale survey across Europe, China and the US.Goal of the survey was to find out about:Citizens' perception about the extent of climate changeCitizens' individual commitments to fight climate changeCitizens' solutions for climate changeResponsibility for fighting climate changeThe findings are particularly relevant at a time when climate is one of the top priorities in the EU's agenda, and following the EIB's adoption of a new, fossil-fuel free energy lending policy and a new climate roadmap.Conducted in partnership with market research firm BVA, the survey aims to inform the broader debate on citizens' attitudes and expectations in terms of climate action in the European Union, the United States and China."Listening to citizens' attitudes is key for us to make sure we address their concerns, while leaving no one behind", Vice-President Emma Navarro